The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/er-08-2017-0188
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HR development on innovative performances in central and eastern European countries

Abstract: Purpose The purpose of this paper is to research the impact of one of HRM activities, employees’ development, on the level of organizational innovative performances. HR development techniques that organizations use in order to develop employee’s knowledge, skills and abilities and their impact on the perceived level of organizational innovativeness was set in the focus of research, with the intent of determining which development techniques influence organizational innovative performance. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 113 publications
(147 reference statements)
1
20
0
5
Order By: Relevance
“…Stressors related to career/job insecurity affect self-esteem [43], and they can lead to serious health complications: organizational factors-organizational structure, culture, changes, communication, and performance [44]. Stress is a partial mediator in the relationship between the challenges in the work-home relation and job satisfaction [45].…”
Section: Stress In Organizationmentioning
confidence: 99%
“…Stressors related to career/job insecurity affect self-esteem [43], and they can lead to serious health complications: organizational factors-organizational structure, culture, changes, communication, and performance [44]. Stress is a partial mediator in the relationship between the challenges in the work-home relation and job satisfaction [45].…”
Section: Stress In Organizationmentioning
confidence: 99%
“…Research carried out in Eastern European countries indicated the existence of relationship between the usage of HR development practices and the level of innovativeness of organizations (Berber and Lekovic, 2018). T&D can improve innovative employees' behaviour, but the relation is mediated by employee's affective commitment (Susomrith et.al., 2019).…”
Section: Hrm Functions: Literature Reviewmentioning
confidence: 99%
“…employees training must be understood as the development of "assets" and not as an expense that has to be reduced [12]. Also, the role of training has changed so today it is viewed not only as "a way to enhance individual capabilities but also as a valuable lever for improving team effectiveness and for organizations to gain competitive advantage" [20][21][22].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many researches in the past have been conducted with the aim of proving the positive and significant relationship between training and development activities and organizational performances [21][22][23][24][25][26][27]. It is confirmed that training programs can help employees in achieving better knowledge, skills and abilities, and, on that basis, higher performances.…”
Section: Relationship Between Training Productivity and Service Qualitymentioning
confidence: 99%